Rhodiola crenulata polysaccharide alleviates dextran sulfate sodium-induced ulcerative colitis in mice by repairing the intestinal barrier and regulating the intestinal microecology - Lv, Jia; Kong, Xinyu; Liu, Wenjun; Su, Zhenzhen; Luo, Fengshou; Suo, Fengtai; Wang, Zhenzhong; Cao, Liang; Liu, Zhongqiu; Li, Mengxuan; Xiao, Wei (Frontiers in Pharmacology, 2025)
Polysaccharides, vital biological macromolecules ubiquitous in organisms, have garnered attention as potential therapeutic candidates for ulcerative colitis (UC). However, the therapeutic potential of Rhodiola crenulata polysaccharides (RCP) in UC remains largely unexplored. The RCP was prepared by boiling water extraction, 80% alcohol precipitation, membrane separation, and D101 macroporous resin purification. The monosaccharide composition of RCP (Mw = 67.848 kDa) includes mannose, rhamnose, glucuronic acid, galacturonic acid, glucose, galactose, and arabinose, with a molar ratio of 0.22:1:0.07:7.03:2.88:0.64:4.12. In vivo experiments have shown that RCP can improve DSS induced weight loss in UC mice, decrease disease activity index (DAI), alleviate histopathological changes in colon tissue, and suppress the levels of pro-inflammatory cytokine IL-6 and MPO activity. Immunohistochemical results showed that essential tight junction proteins such as occludin, claudin1, and ZO-1 were upregulated, improving the integrity of the intestinal barrier. Importantly, RCP regulated the abundance of the intestinal microbiota by reducing the Firmicutes-to-Bacteroidetes ratio (F/B), increasing beneficial bacteria such as Muribaculaceae and Bifidobacterium, decreasing harmful bacteria including Erysipelotrichaceae, Faecalibaculum, Lachnospiraceae_unclassified, Parabacteroides, and Ruminiclostridium_9. Additionally, it enhanced the restoration of acetic acid, propionic acid, isovaleric acid, and valeric acid to maintain intestinal SCFA levels, thereby restoring the intestinal microecology. Therefore, RCP has excellent therapeutic effects on UC and is worthy of further drug development and clinical treatment.